Art and the senses - Bacci, Francesca, 1972-; Melcher, David (Oxford : Oxford University Press, 2011)
The senses play a vital role in our health, our social interactions, and in enjoying food, music and the arts. The book provides an interdisciplinary overview of the senses, ranging from the neuroscience of sensory processing in the body, to the role of the senses in the arts.
Includes bibliographical references and index.
boek